1998
DOI: 10.2527/1998.7671887x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrates alter the fecal composition and pH and the ammonia emission from slurry of growing pigs.

Abstract: We investigated the effects of dietary carbohydrates on the composition and pH of fecal material and on the ammonia emission from the slurry of growing pigs. Thirty-four barrows (BW approximately 40 kg) were randomly allotted to 1 of 10 diets. A basal diet was formulated to meet all requirements for protein, amino acids, minerals, and vitamins. The control diet was composed of the basal diet plus heat-treated cornstarch. In the other diets, the cornstarch in the control diet was replaced with three levels of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
82
4
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(104 citation statements)
references
References 10 publications
9
82
4
9
Order By: Relevance
“…Apparent faecal nitrogen digestibility was, however, much lower in S-housed pigs than in B-housed pigs in the present study . This likely results from a shift from excretion of nitrogen from urine to faeces due to an increased amount of fermentable substrate in the colon (Heijnen and Beynen, 1997;Canh et al, 1998), and may therefore not be present at the ileal level.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent faecal nitrogen digestibility was, however, much lower in S-housed pigs than in B-housed pigs in the present study . This likely results from a shift from excretion of nitrogen from urine to faeces due to an increased amount of fermentable substrate in the colon (Heijnen and Beynen, 1997;Canh et al, 1998), and may therefore not be present at the ileal level.…”
Section: Discussionmentioning
confidence: 99%
“…However, decreases in ammonia emission have been reported when sources of fermentable fibre are added to the diet (Canh et al, 1998) and barley b-glucans have been shown to have pre-biotic properties (O'Connell et al, 2005). By increasing carbohydrate fermentation and limiting protein fermentation in the large intestine, the production of some of the most offensive VFAs can be reduced (Mackie et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fibre also provides a non-nitrogen containing energy source to distal bacteria so that the distal nitrogen sources are used for bacterial protein synthesis rather than energy yielding ammonia (Canh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It could also be that we did not measure the main odorous compounds that determine the odour threshold. According to Canh et al (1998c) fermentable NSP are the most important dietary components determining VFA concentration in the manure. The VFA pool was largely dominated by the short straight -chain VFA such as acetic, propionic and butyric acids which comprised 91% of total VFA in the manure confirming the results of Otto et al (2003) and Le et al (2005a).…”
Section: Discussionmentioning
confidence: 99%